Lorentzian Para-Kenmotsu Manifolds Within the Framework of ∗-Conformal η-Ricci Soliton - Shyam Kishor; Arun Kumar Bhardwaj; Naveen Mani; Rahul Shukla (Journal of Applied Mathematics)
The present article intends to study the ∗-conformal η-Ricci soliton on n-LPK (n-dimensional Lorentzian para-Kenmotsu) manifolds with curvature constraints. On n-LPK, we derive certain results of ∗-conformal η-Ricci soliton satisfying the Codazzi-type equation, Rξ,L·S=0, the projective flatness of the n-LPK manifold. At last, we conclude with an n-LPK manifold with conformal η-Ricci solitons using a suitable example.